Potencialidades de argilas bentoníticas naturais e organofílicas da paraíba para aplicação cosmética - Cavalcanti, Roberta Kelly Bondade De Caldas (2016)
Mineral makeup is a cosmetic formulation that brings among its components mineral raw materials example of clay materials in this context refers to the bentonite as the most commonly used clays. Its technological features already known commercially, support a strong indication of positive use this as an asset in formulations for mineral makeup. In this sense, the use of bentonite clays of Paraíba State in the development of mineral powder formulations for makeup was the central objective of this work. It was initially performed the physicochemical characterization of the natural bentonite clays and organoclays, the results indicate that the clays have potential technological profile with cosmetic, with a low and narrow range of particle size, aceitávell oil adsorption capacity and flow property as expected for these clays, allowing the formulations were developed for the study. Cosmetic formulation was used 50% of each of clays and other mineral components, giving rise to six different formulations. From these samples was studied its stable front behavior at extreme conditions through accelerated stability test under freezing cycles at ± 5 ° C and heating at ± 50 ° C developed according to the methods of ANVISA properties were subsequently verified flow and organoleptic characteristics of the product. The control of toxicological and microbiological quality was performed according to the standards set by ANVISA and the Brazilian Pharmacopoeia. Samples were tested to investigate the ophthalmic irritability by in vitro assay of chicken egg chorioallantoic membrane (HET-CAM) and microbiological testing was done by the plating method on the surface. All samples were stable as its physical and chemical characteristics and no change in color, appearance and odor was observed. None of the formulations showed cytotoxicity to the respective concentrations of the formulations. The microbiological control ensures the biological safety of the material in relation to the absence of bacteria.